Volumetric Structural Magnetic Resonance Imaging Findings in Pediatric Posttraumatic Stress Disorder and Obsessive Compulsive Disorder: A Systematic Review - Ahmed, Fatima; Ras, Johan; Seedat, Soraya (Frontiers in Psychology, 2012)
Objectives: Structural magnetic resonance imaging (sMRI) studies of anxiety disorders in children and adolescents are limited. Posttraumatic stress disorder (PTSD) and obsessive-compulsive disorder (OCD) have been best studied in this regard. We systematically reviewed structural neuroimaging findings in pediatric PTSD and OCD. Methods: The literature was reviewed for all sMRI studies examining volumetric parameters using PubMed, ScienceDirect and PsychInfo databases, with no limit on the time frame of publication. Nine studies in pediatric PTSD and 6 in OCD were suitable for inclusion. Results: Volumetric findings were inconsistent in both disorders. In PTSD, findings suggest increased as well as decreased volumes of the prefrontal cortex (PFC) and corpus callosum; whilst in OCD studies indicate volumetric increase of the putamen, with inconsistent findings for the anterior cingulate cortex (ACC) and frontal regions. Conclusions: Methodological differences may account for some of this inconsistency and additional volume-based studies in pediatric anxiety disorders using more uniform approaches are needed.